Ozone absorption in a mechanically stirred reactor - Takić Ljiljana; Veljković Vlada; Lazić Miodrag; Pejanović Srđan (Journal of the Serbian Chemical Society, 2007)
Ozone absorption in water was investigated in a mechanically stirred reactor, using both the semi-batch and continuous mode of operation. A model for the precise determination of the volumetric mass transfer coefficient in open tanks without the necessity of the measurement the ozone concentration in the outlet gas was developed. It was found that slow ozone reactions in the liquid phase, including the decomposition of ozone, can be regarded as one pseudo-first order reaction. Under the examined operating conditions, the liquid phase was completely mixed, while mixing in a gas phase can be described as plug flow. The volumetric mass transfer coefficient was found to vary with the square of the impeller speed. .